2020
DOI: 10.1080/22221751.2020.1821582
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of emerging ESBL-producing Salmonella Kentucky bla CTX-M-14b in Europe

Abstract: Global dissemination of ciprofloxacin-resistant Salmonella Kentucky has been observed over the past decades. In recent years, there have been reports of extended-spectrum β-lactamase (ESBL) producing S . Kentucky. Routine surveillance at the European Centre for Disease Prevention and Control (ECDC) detected cases with a ciprofloxacin-resistant S . Kentucky with the ESBL-gene bla CTX-M-14b . Ensuing research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 48 publications
4
49
1
1
Order By: Relevance
“…Acquisition of SGI1 and plasmids, as well as mutations in the QRDR, were the only genetic features found during this study to explain the global epidemiological success of the MDR S. Kentucky ST198 lineage which is highly resistant to ciprofloxacin. Coipan et al (2020) describe how a clone of this lineage, with an ESBL-gene (bla CTX-M-14b ) incorporated on the chromosome, has emerged in Europe. In contrast to plasmid-mediated resistance, chromosomal-mediated resistance is most likely to be maintained also without antibiotic pressure, especially if it incurs no fitness cost for the bacteria.…”
Section: Susceptibility Testing Of Mrsa Isolates Obtained From Meat and Food-producing Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquisition of SGI1 and plasmids, as well as mutations in the QRDR, were the only genetic features found during this study to explain the global epidemiological success of the MDR S. Kentucky ST198 lineage which is highly resistant to ciprofloxacin. Coipan et al (2020) describe how a clone of this lineage, with an ESBL-gene (bla CTX-M-14b ) incorporated on the chromosome, has emerged in Europe. In contrast to plasmid-mediated resistance, chromosomal-mediated resistance is most likely to be maintained also without antibiotic pressure, especially if it incurs no fitness cost for the bacteria.…”
Section: Susceptibility Testing Of Mrsa Isolates Obtained From Meat and Food-producing Animalsmentioning
confidence: 99%
“…The proportion of S. Kentucky with an ESBL phenotype decreased from 20.3% in 2017 to 5.6% in 2019, with four countries (Germany, France, Malta and the Netherlands) reporting presumptive ESBL-producing S. Kentucky in 2019. The introduction and spread of S. Kentucky with bla CTX-M-14b in Europe has recently been described by Coipan et al (2020). During this study, conducted over the period 2013-2018, 78 human cases of S. Kentucky harbouring the bla CTX-M-14b gene (as well as displaying gyrA and parC mutations associated with ciprofloxacin resistance) were identified in eight European countries (comprising the United Kingdom, Malta, the Netherlands, Germany, Belgium, Denmark, Norway and Ireland).…”
Section: Occurrence Of Resistance To 'Critically Important Antimicrobials' (Cias)mentioning
confidence: 99%
“…Interestingly, ESBL production correlates with certain serovars in S. enterica. Among serovars found in human infections, ESBL genes have been more frequently detected in S. Typhimurium, S. Infantis and S. Kentucky than in S. Enteritidis [5,14]. Furthermore, recent analyses on ESBL-producing S. Infantis from broiler chickens, broiler meat, and humans revealed a clonal lineage harbouring an especially successful conjugative pESI-like plasmid [15].…”
Section: Introductionmentioning
confidence: 99%
“…With the hybrid assemblies obtained with the workflow, it was determined that in the Belgian S. Kentucky isolates, the ESBL genes were present on both the chromosome and on plasmids and that there was also a likely exchange by a transposase of a 2850 bp region between the chromosome and a plasmid of different isolates. The results of our workflow on the Belgian isolates, and especially of the plasmid reconstruction, were put into epidemiological context of the other European Salmonella Kentucky ESBL-positive isolates by Coipan et al [83]. They found that this 2850 bp fragment was present in the chromosome and plasmids of other S. Kentucky isolates [83].…”
Section: Discussionmentioning
confidence: 82%
“…The results of our workflow on the Belgian isolates, and especially of the plasmid reconstruction, were put into epidemiological context of the other European Salmonella Kentucky ESBL-positive isolates by Coipan et al [83]. They found that this 2850 bp fragment was present in the chromosome and plasmids of other S. Kentucky isolates [83]. The exchanged fragment is very similar to that on the chromosome of an S. Kentucky isolated from poultry in China [64]; however, the exact sequence reported in the Chinese study is not yet available in public databases to make the full comparison.…”
Section: Discussionmentioning
confidence: 99%